Togo – 2013: Politics, economy and society in 2013 - Dirk Kohnert (Africa Yearbook Volume 10: Politics, Economy and Society South of the Sahara in 2013, 2014)
Peaceful but undemocratic legislative elections consolidated the power of the Gnassingbé regime in 2013. In view of the absolute majority gained by the ruling party, its inclination to implement meaningful reforms, as demanded by the opposition and the donor community, was reduced further. The growing Islamist threats in neighbouring countries meant that the donor community condoned the delays in democratic reforms including the conduct of local elections, which were pushed back several times. Promising growth prospects were overshadowed by increasing poverty and inequality. – – Friedliche, aber undemokratische Parlamentswahlen festigten 2013 die Macht des Gnassingbé-Regimes. Angesichts der absoluten Mehrheit der Regierungspartei nahm ihre Bereitschaft, sinnvolle Reformen umzusetzen, wie von der Opposition und der Gebergemeinschaft gefordert, weiter ab. Angesichts der wachsenden islamistischen Bedrohung in den Nachbarländern duldete die Gebergemeinschaft die Verzögerungen bei demokratischen Reformen, einschließlich der Durchführung lokaler Wahlen, die mehrmals verschoben wurden. Vielversprechende Wachstumsaussichten wurden durch zunehmende Armut und Ungleichheit überschattet.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2013; domestic policy; foreign affairs; socio-economic development; period under review 2013